Analysis of the Impact of Symmetrical Auto Rejection Policy on IHSG Movement on the IDX During 2020-2023 - Maudya, Intan yhejri Rari; Yuliati, Y. (Golden Ratio of Finance Management, 2025)
This study analyzes the market response to the change in auto rejection policy from 15% to symmetric auto rejection implemented by the Indonesia Stock Exchange (IDX) in 2020-2023. This policy aims to maintain market stability and protect investors from extreme price fluctuations. This study uses a quantitative method with the Wilcoxon Signed Rank test to analyze differences in abnormal returns and trading volume before and after implementing the policy. The sample consists of 48 companies listed on the IDX for 3 periods, selected purposively from various sectors. The results showed significant differences in both variables. The market response to abnormal returns showed a positive signal, while trading volume reflected an adverse reaction, illustrating the negative market sentiment towards this policy. This finding confirms that policy changes have a significant impact on investor behavior. The author advises investors to conduct in-depth fundamental and technical analysis to understand the entire policy and minimize the risk of loss in making investment decisions.